Physicochemical characterization of Suvarna Bhasma, its toxicity profiling in rat and behavioural assessment in zebrafish model. (1st March 2020) - Biswas, Snehasis; Dhumal, Rohit; Selkar, Nilakash; Bhagat, Sharad; Chawda, Mukesh; Thakur, Kapil; Gudi, Ramacharya; Vanage, Geeta; Bellare, Jayesh
Abstract: Ethnopharmacological relevance: Suvarna Bhasma is a gold-based Ayurved medicine that has a wide range of therapeutic indications like tuberculosis, diabetes mellitus, rheumatoid arthritis and nervous diseases. Suvarna Bhasma is also used in Suvarnaprashana, an Ayurved advocated therapy being practised to improve immunity in children. Aim of the study: To augment traditional understanding, here we present an evidence-based study on Suvarna Bhasma regarding its physicochemical properties, toxicity and efficacy. Materials and methods: Suvarna Bhasma was characterised by physicochemical characterization techniques such as scanning electron microscope (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and atomic emission spectroscopy (ICP-AES). Toxicity of Suvarna Bhasma was studied in Holtzman rats with daily oral dose from 3 mg/kg (therapeutic dose, TD) up to 30 mg/kg (10 TD) body weight for 90 days. Behavioural study, such as motor and geotactic behaviour were examined in zebrafish model to find out any sign of neurotoxicity or behavioural changes due to Suvarna Bhasma administration. Results: Suvarna Bhasma has two types of gold particles, large ones ( 60 μm) having irregular shapes, and nano-sized spherical particles (starting from 10 nm), the latter coated with Fe, Si, O, P and Na. XRD study revealed that all the peaks of Suvarna Bhasma match well with pure gold (face centred cube) with crystallites size 45 ± 2.8 nm. In rat studies, some change in biochemical parameters such as urea, creatinine and alanine aminotransferase (ALT) was observed mainly at the higher therapeutic dose; however, those parameters were within the normal range. There were no significant macroscopic as well as microscopic treatment-related alteration observed, in any of the organs and tissues evaluated. In zebrafish behavioural study, the motor parameters of Suvarna Bhasma treated fish showed normal behaviour analogous to the vehicle control group. Interestingly, the geotactic behaviour showed anxiolytic effects of Suvarna Bhasma as evidenced by the time spent in the upper zone, and average swimming height. The anxiolytic effects persisted for more than 30 days after withdrawing the Suvarna Bhasma treatment. Conclusions: Suvarna Bhasma contained spherical gold nanoparticles. It was nontoxic in rat model at the does tested. Suvarna Bhasma has anxiolytic effects in zebrafish behavioural model. Graphical abstract: Image 1